Hindu Pluralism Religion and the Public Sphere in Early Modern South India - Fisher, Elaine (University of California Press, 2017)
In Hindu Pluralism, Elaine M. Fisher complicates the traditional scholarly narrative of the unification of Hinduism. By calling into question the colonial categories implicit in the term "sectarianism," Fisher's work excavates the pluralistic textures of precolonial Hinduism in the centuries prior to British intervention. Drawing on previously unpublished sources in Sanskrit, Tamil, and Telugu, Fisher argues that the performance of plural religious identities in public space in Indian early modernity paved the way for the emergence of a distinctively non-Western form of religious pluralism. This work provides a critical resource for understanding how Hinduism developed in the early modern period, a crucial era that set the tenor for religion's role in public life in India through the present day. "A detailed, insightful, and original perspective on a significant and understudied period. It engages intelligently with current discussions of early modern Indian intellectual and religious history, while calling into question key elements of the existing picture of the period among specialists in the field." -LAWRENCE McCREA, Cornell University "Fisher works at both a micro and macro level to read the intricacies of Smarta Saivism against the broader backdrop of evolving definitions of Hinduism. Her counterintuitive thesis is that sectarianism is not so much a breakup of a preexisting unity but rather an aggregation of discrete religions." -GAURI VISWANATHAN, Columbia University "Fisher's work is critical now more than ever in helping us to understand what Hinduism is and how it began to be that way, not in misty antiquity but in early modernity." -ROBERT P. GOLDMAN, University of California at Berkeley ELAINE M. FISHER is Assistant Professor in the Department of Religious Studies at Stanford University.